SiSTEM INFORMASI MANAJEMEN CUTI PEGAWAI BERBASIS WEBSITE PADA PROSUS INTEN JAKARTA - Fitriani, Yuni; Rahayu, Luci Kanti; Emiliya, Devi; Syabani, Khofifah Nur; Nabilla, Rizki (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Companies are required to utilize information technology to manage their operational activities more effectively and efficiently. One key aspect of company operational management is employee leave management. Leave refers to a situation where an employee is absent from work due to annual leave, maternity leave, vacations, or other personal reasons that have been officially approved for a specified period. At Prosus Inten, the current process of managing employee leave is still less effective and efficient, as employees must directly contact the attendance management team when submitting a leave request. Consequently, the attendance manager must compile daily attendance records by reviewing and verifying attendance data from emails, as well as checking the list of employees who have submitted leave requests. The system development model used in this study is the waterfall model. With the implementation of a web-based employee leave management information system, Prosus Inten is assisted in the management of employee leave, and employees are aided in the leave request submission process. Furthermore, the system enables employees to conveniently track their remaining leave balance as well as the number of leave days already used.